Pulse duration settings in subthalamic stimulation for Parkinson's disease. Issue 1 (22nd November 2017) - Steigerwald, Frank; Timmermann, Lars; Kühn, Andrea; Schnitzler, Alfons; Reich, Martin M.; Kirsch, Anna Dalal; Barbe, Michael Thomas; Visser‐Vandewalle, Veerle; Hübl, Julius; van Riesen, Christoph; Groiss, Stefan Jun; Moldovan, Alexia‐Sabine; et al.
ABSTRACT: Background: Stimulation parameters in deep brain stimulation (DBS) of the subthalamic nucleus for Parkinson's disease (PD) are rarely tested in double‐blind conditions. Evidence‐based recommendations on optimal stimulator settings are needed. Results from the CUSTOM‐DBS study are reported, comparing 2 pulse durations. Methods: A total of 15 patients were programmed using a pulse width of 30 µs (test) or 60 µs (control). Efficacy and side‐effect thresholds and unified PD rating scale (UPDRS) III were measured in meds‐off (primary outcome). The therapeutic window was the difference between patients' efficacy and side effect thresholds. Results: The therapeutic window was significantly larger at 30 µs than 60 µs ( P = ·0009) and the efficacy (UPDRS III score) was noninferior ( P = .00008). Interpretation: Subthalamic neurostimulation at 30 µs versus 60 µs pulse width is equally effective on PD motor signs, is more energy efficient, and has less likelihood of stimulation‐related side effects. © 2017 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.